The first reported artificial propagation of yellow puffer, Xenopterus naritus (Richardson, 1848) from Sarawak, Northwestern Borneo - Ahmad Syafiq, Ahmad Nasir; Samsur, Mohamad; Mohammed, Mohidin (Blackwell Publishing Ltd, 2017)
Pufferfish from family Tetraodontidae consists of 28 genera and 199 species worldwide, distributed in tropical and subtropical areas of Atlantic, Indian and Pacific Ocean (Nelson 1994). Some pufferfish species has become targeted species for aquaculture industry in various country including Japan, China, South Korea and Mexico. Reproductive biology of these valuable aquaculture species including tawny puffer (Shi, Zhang, Liu & Zang 2011), obscure puffer (Won, Kim & Park 2009; Kim, Dahms & Han 2013), tiger puffer (Wu, Tang, Yuan, Shi, Shakeela & Zhang 2015) and bullseye puffer (Sanchez, Alvarez-Lajonchere, Abdo De La Parra & Garcia 2008; Abdo-de La Parra, Garcıa- Ortega, Martınez-Rodrıguez, Gonzalez-Rodrıguez, Velasco-Blanco, Hernandez & Duncan 2010) has been studied extensively for optimizing the production in aquaculture. In Sarawak coastal waters, there are 13 species of six genera of marine pufferfish species that has been reported (Vidthayanon 1998). Most of these species are non-target species in capture fisheries and has been considered as trash fish. However, there is one native pufferfish species that is widely consumed by the locals which is yellow puffer, X. naritus. Despite its lethality (Mohd Nor Azman, Samsur & Othman 2014), this species is considered as highly sought after delicacy due to the tenderness of their meat according to the locals.